Macrovascular and renal microvascular complications in West Africans with intermediate hyperglycemia living in West Africa and Europe: The RODAM study - Bannerman-Williams, Emmanuel; Hayfron-Benjamin, Charles F.; Atiase, Yacoba; Bahendeka, Silver; Meeks, Karlijn; Klipstein-Grobusch, Kerstin; Addo, Juliet; Mockenhaupt, Frank; Schulze, Matthias B.; Beune, Erik; van den Born, Bert-Jan; Agyemang, Charles (Heliyon, 2023)
Metabolic conditions, including intermediate hyperglycemia (IH), affect migrants to a greater extent than the populations of origin. Evidence suggests that IH increases the risk of vascular complications, but it is unclear whether the differences in IH between the non-migrant and migrant populations translate to differences in vascular complications between the two populations. We compared the prevalence of macrovascular and renal microvascular complications among West Africans with IH living in West Africa and their migrant compatriots in Europe. Data from the multicenter Research on Obesity and Diabetes among African Migrants(RODAM) study were analyzed. Ghanaians with IH(524 non-migrant and 1439 migrants) were included. Logistic regression analyses were used to determine the associations between migrant status and macrovascular [coronary artery disease(CAD) and peripheral artery disease(PAD)] and renal microvascular[nephropathy] complications with adjustment for age, sex, socioeconomic status, smoking, systolic blood pressure, BMI, total cholesterol, HbA1c, C-reactive protein, and serum uric acid. The prevalence of microvascular/macrovascular complications was higher in non-migrants than in migrants(nephropathy 15.3vs.9.7%; PAD 3.1%vs.1.3%; and CAD 15.8% vs. 5.0%). The differences persisted in the fully adjusted model: nephropathy [odds ratio, 2.12; 95% CI(1.46–3.08); PAD, 4.44(1.87–10.51); CAD 2.35(1.64–3.37)]. Non-migrant females had higher odds of nephropathy[2.14(1.34–3.43)], PAD[7.47(2.38–23.40)] and CAD [2.10(1.34–3.27)] compared to migrant females. Non-migrant males had higher odds of nephropathy[2.54(1.30–4.97)] and CAD[2.85(1.48–5.50)], but not PAD[1.81(0.32–10.29)],than their migrant peers. Macrovascular and renal microvascular complications were more prevalent in non-migrants than in migrant West Africans with IH. Further studies are needed to identify factors that increase the risk to aid preventive/treatment strategies.